MEASUREMENT OF ABSORPTIVE CAPACITY IMPLICATIONS IN SMALL AND MEDIUM INDUSTRIES : (Case in Ngingas Small Logam Industry Cluster) - Gogor Arif , Handiwibowo (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2025)
The post-covid-19 era is a momentum for all types of business models to immediately reach their highest performance after dropping drastically due to the economic recession. The manufacturing industry is one type of business model that is under enormous pressure during Covid-19 and is required to immediately return to normal. Small and medium industries as a class of manufacturing industry are unique in their ability to recover quickly, apart from the fact that their industrial model is quite small, many of these small and medium industries also form industrial clusters. In the current era of knowledge-based economy, one theory provides an illustration that if a business organization wants to quickly achieve business performance, it needs to master the necessary knowledge. This concept is called absorptive capacity which explains how a business organization acquires knowledge and implements it to gain competitive advantage. This research tries to present a factor analysis on the theoretical concept of absorptive capacity (with the dimensions of acquisition, assimilation, transformation, and exploitation) in a small and medium industrial cluster. There were 127 respondents from the small and medium Logam industrial cluster in Ngingas Village, Waru Distric, Sidoarjo - Indonesia. This research reveals that in the small and medium Logam industrial cluster in Ngingas Waru Sidoarjo - Indonesia, the acquisition factor is the dominant factor in the process of mastering knowledge that comes from outside the organization and the assimilation factor is the least dominant factor in the process of mastering knowledge.